Daily physical activity and physical function in adult maintenance hemodialysis patients. Issue 3 (29th April 2014) - Kim, J. C.; Shapiro, B. B.; Zhang, M.; Li, Y.; Porszasz, J.; Bross, R.; Feroze, U.; Upreti, R.; Kalantar-Zadeh, K.; Kopple, J. D.
Abstract : Background: Maintenance hemodialysis (MHD) patients reportedly display reduced daily physical activity (DPA) and physical performance. Low daily physical activity and decreased physical performance are each associated with worse outcomes in chronic kidney disease patients. Although daily physical activity and physical performance might be expected to be related, few studies have examined such relationships in MHD patients, and methods for examining daily physical activity often utilized questionnaires rather than activity monitors. We hypothesized that daily physical activity and physical performance are reduced and correlated with each other even in relatively healthier MHD patients. Methods: Daily physical activity, 6‐min walk distance (6‐MWT), sit‐to‐stand, and stair‐climbing tests were measured in 72 MHD patients (32 % diabetics) with limited comorbidities and 39 normal adults of similar age and gender mix. Daily physical activity was examined by a physical activity monitor. The human activity profile was also employed. Results: Daily physical activity with the activity monitor, time‐averaged over 7 days, and all three physical performance tests were impaired in MHD patients, to about 60–70 % of normal values ( p  < 0.0001 for each measurement). Human activity profile scores were also impaired ( p  < 0.0001). MHD patients spent more time sleeping or in marked physical inactivity ( p  < 0.0001) and less time in ≥ moderate activity ( p  < 0.0001). These findings persisted when comparisons to normals were restricted to men or women separately. After adjustment, daily physical activity correlated with 6‐MWT but not the two other physical performance tests. Human activity profile scores correlated more closely with all three performance tests than did DPA. Conclusions: Even in relatively healthy MHD patients, daily physical activity and physical performance are substantially impaired and correlated. Whether training that increases daily physical activity or physical performance will improve clinical outcome in MHD patients needs to be examined.